Antigenic cells augment CAR T cells - Skinner, Pamela J. (Blood, 2020)
Innovations in chimeric antigen receptor (CAR) T-cell immunotherapies are at the forefront of new treatments for HIV infections. In this issue of Blood, Rust et al describe new innovations in CAR T-cell immunotherapy to treat HIV that led to profound expansion and improved function of CAR T cells in vivo.(1)